Melanoma induced immunosuppression is mediated by hematopoietic dysregulation. (4th March 2018) - Kamran, Neha; Li, Youping; Sierra, Maria; Alghamri, Mahmoud S.; Kadiyala, Padma; Appelman, Henry D.; Edwards, Marta; Lowenstein, Pedro R.; Castro, Maria G.
ABSTRACT: Tumors are associated with expansion of immunosuppressive cells such as tumor associated macrophages (TAMs), regulatory T cells (Tregs) and myeloid derived suppressor cells (MDSCs). These cells promote tumor growth, angiogenesis, metastasis and immune escape. Cancer patients frequently present symptoms such as anemia, leukocytosis and/or cytopenia; associated with poor prognosis. To uncover tumor-mediated hematopoietic abnormalities and identify novel targets that can be harnessed to improve tumor-specific immune responses, we investigated the hematopoietic stem and progenitor cell compartment in melanoma bearing mice. We show that melanoma growth results in expansion of myeloid lineages such as MDSCs, macrophages and DCs along with a reduction in mature RBCs and platelets. Mature B lymphocytes in the blood and BM of melanoma mice were also reduced. Mice bearing melanoma showed extramedullary hematopoiesis in the spleen. Increased expansion of myeloid lineages occurred directly at the level of stem and progenitor cells. The reduction in mature B lymphocytes resulted from a block at the Pro-B cell stage in the bone marrow. Addition of recombinant IL-3 to bone marrow cells resulted in the expansion of committed myeloid progenitors including common myeloid precursors, granulocyte-monocyte precursors and megakaryocyte-erythrocyte precursors. In vivo, IL-3 receptor stimulation in melanoma bearing mice using an IL-3 antibody also resulted in a robust expansion of committed myeloid progenitors and hematopoietic stem cells. Collectively our findings demonstrate that tumor growth plays a pivotal role in reprogramming the host immune system by impacting hematopoiesis directly at the level of stem cell compartment.